Do healthcare personnel promote organisational citizenship behaviours? - Othman, Noraini (Universiti Utara Malaysia, 2006)
Healthcare services in Malaysia have evolved over the past century to becomen among the best in the world, although with strenuous working conditions to the heathcare personnel.This situation, however, provides an interesting avenue to understand whether nurses in the public sector exhibit organisational citizenship behaviours (OCB) amid the working environment that hampers such behaviours.This study explores the OCB practices amongst public heathcare nurses in Malaysia. In general, this study has found that nurses do display OCB in their daily work practices.Results from the 727 respondents indicated that there were no significant relationships between demographic variables and OCB,consistent with earlier studies in this field.The study also found that there were significant relationships between job satisfaction and OCB, and between organisational commitment and OCB.These results indicated that job satisfaction and organisational commitment contributed significantly to the prediction of OCB.Further investigation into each dimension of OCB has found that altruism or helping behaviour had the lowest score and this suggested a contradictory description of job and gender.